The development of science academic word list - It-ngam, Todsaporn; Phoocharoensil, Supakorn (Universitas Pendidikan Indonesia, 2019)
Knowledge of specialized academic vocabulary is important for the academic success of EFL natural science students. Specialized words outside the General Service List (GSL) (West, 1953) and the Academic Word List (AWL) (Coxhead, 2000) are necessary for comprehending scientific text. The existing lists of words do not cover all sub-disciplines of natural science. The present study aims to explore the specialized academic words across 11 sub-disciplines of natural science. To identify the words, a corpus-based approach and an expert-judged approach were used. A 5.5-million-word corpus called the Science Academic Journal (SAJ) Corpus was created for this study. Applying the established word selection criteria, 513 word families were selected. The potential list was reviewed by a panel of experts in order to remove the overly-technical words from the list. The Science Academic Word List (SAWL) was established with 432 word families and provided 5.82% coverage of the running words in the SAJ corpus. To validate the word list, the SAWL was tested against two independent corpora. The findings revealed that the SAWL contains 432 word families that are useful for reading journal articles in natural science disciplines. In addition, it was also found that the SAWL performed better on an independent corpus compared to the Science World List (Coxhead Hirsh, 2007). It is expected that the SAWL established in this study will be a useful source for learning and teaching vocabulary in natural science disciplines.